Implementasi Algoritma IWD dalam Aplikasi Mobile untuk Penentuan Rute Travel - Indra Maryati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Transportation has turned into a primary need, such as ride-hailing, inter-city travel, and even pick-up and drop-off for schools or employees, which are much sought after. This type of transportation is very popular because it provides flexibility in pick-up and drop-off locations. On the shuttle vehicle there will be several customers where the driver has to think of the most efficient route to pick-up. To efficiently find the routes, the driver will need quite a long time and extensive knowledge about the location. A system that can determine pick-up and drop-off routes is certainly needed by the driver. System is equipped with navigation features to make it easier for drivers to done pick-up. In completing this system, Intelligent Water Drops (IWD) algorithm will be used to determine the pick-up or drop-off route. The process of master data, reports, running IWD to find the best route is carried out by an admin. Best route result will be sent to the mobile application used by driver, there will be a navigation feature using Google Maps that can be used by the driver. With the system created, it can help drivers finish their work of pick-up and drop-off costumer in better efficiency of time and distance. With the help of Google Maps, the driver can also find out the duration of the pick-up or drop-off and the traffic conditions.